1986
DOI: 10.1530/jrf.0.0780275
|View full text |Cite
|
Sign up to set email alerts
|

A role for alternative pathway catecholamines in the regulation of steroidogenesis in cow luteal cells

Abstract: Summary. Incubation of bovine luteal cells with the alternative pathway catecholamines octopamine, synephrine and deoxyadrenaline at concentrations of 10 \ m=-\ 6 to 10\m=-\3 m enhanced the production of progesterone (P < 0\m=.\05).Tryamine did not alter basal progesterone production (P > 0\m=.\05). Addition of noradrenaline and adrenaline at concentrations of 10 \ m=-\ 4 to 10\m=-\7 m significantly elevated the production of progesterone (P < 0\m=.\05). The steroidogenic response to noradrenaline and adrenali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1987
1987
2001
2001

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Condon and Black [85] demonstrated that catecholamines stimulate P4 secretion in bovine CL in vitro. This observation was confirmed by many experiments both in vitro [20,29,56,82,86,87] and in vivo [31,32,88]. Catecholamines also stimulate the synthesis and release of OT [20,29,31].…”
Section: Noradrenaline As a Luteotropic Factormentioning
confidence: 53%
See 1 more Smart Citation
“…Condon and Black [85] demonstrated that catecholamines stimulate P4 secretion in bovine CL in vitro. This observation was confirmed by many experiments both in vitro [20,29,56,82,86,87] and in vivo [31,32,88]. Catecholamines also stimulate the synthesis and release of OT [20,29,31].…”
Section: Noradrenaline As a Luteotropic Factormentioning
confidence: 53%
“…Noradrenaline regulates the secretory function of bovine CL by activation of β-adrenergic receptors [31,[84][85][86][87][88][89][90][91]. On the other hand, NA can also increase the pressure of the blood supply to the bovine CL by stimulation of β-adrenergic receptors [78][79][80].…”
Section: Noradrenaline As a Luteotropic Factormentioning
confidence: 99%
“…In addition to the absence of direct adrenergic innervation, we have been unable to detect noradrenaline or adrenaline in bovine luteal tissue using HPLC analysis (Battista & Condon, 1986b), but serotonin was detected (Battista & Condon, 1986a). Possible sources of luteal serotonin include mast cells, blood platelets, storage of peripherally circulating serotonin or de-novo syn¬ thesis.…”
Section: Discussionmentioning
confidence: 66%
“…Recently Battista et al (1989) reported similar levels in bovine corpora lutea on days 10-12 of the oestrous cycle (noradrenaline 10-2 + 2-5 ng/g; dopamine 41-9 + 5-7 ng/g). These data provide a physiological basis for the catecholamine stimulation of progesterone and oxytocin synthesis by bovine luteal and granulosa cells (Condon & Black, 1976;Battista & Condon, 1986;Luck & Jungclas, 1987) and for the presence of ß-receptors in luteal tis¬ sue (Abramovitz, Iyengar & Birnbaumer, 1982;Norjavaara, Rosberg, Gäfvels & Selstam, 1984;Perkins, Cronin & Veldhuis, 1986). Further support for the role of catecholamines in luteal function has been demonstrated in vivo by Weiss, Dail & Ratner (1982) who found that electrical stimulation of the superior ovarian nerve enhanced progesterone production in the rat, and also by Burden & Lawrence (1977) who reported that denervation or chemical sympathectomy decreased 3ß-hydroxysteroid dehydrogenase activity in corpora lutea of pregnant rats.…”
Section: Discussionmentioning
confidence: 81%